Folate Intake Alters Mutation Frequency and Profiles in a Tissue- and Dose-Specific Manner in MutaMouse Male Mice. Issue 4 (9th March 2021) - Diaz G, Stephanie; LeBlanc, Danielle P; Gagné, Remi; Behan, Nathalie A; Wong, Alex; Marchetti, Francesco; MacFarlane, Amanda J
ABSTRACT: Background: While cancer is common, its incidence varies widely by tissue. These differences are attributable to variable risk factors, such as environmental exposure, genetic inheritance, and lifetime number of stem cell divisions in a tissue. Folate deficiency is generally associated with increased risk for colorectal cancer (CRC) and acute lymphocytic leukemia (ALL). Conversely, high folic acid (FA) intake has also been associated with higher CRC risk. Objective: Our objective was to compare the effect of folate intake on mutant frequency (MF) and types of mutations in the colon and bone marrow of mice. Methods: Five-week-old MutaMouse male mice were fed a deficient (0 mg FA/kg), control (2 mg FA/kg), or supplemented (8 mg FA/kg) diet for 20 wk. Tissue MF was assessed using the lacZ mutant assay and comparisons made by 2-factor ANOVA. LacZ mutant plaques were sequenced using next-generation sequencing, and diet-specific mutation profiles within each tissue were compared by Fisher's exact test. Results: In the colon, the MF was 1.5-fold and 1.3-fold higher in mice fed the supplemented diet compared with mice fed the control ( P = 0.001) and deficient ( P = 0.008) diets, respectively. This contrasted with the bone marrow MF in the same mice where the MF was 1.7-fold and 1.6-fold higher in mice fed the deficient diet compared with mice fed the control ( P = 0.02) and supplemented ( P = 0.03) diets, respectively. Mutation profiles and signatures (mutation context) were tissue-specific. Conclusions: Our data indicate that dietary folate intake affects mutagenesis in a tissue- and dose-specific manner in mice. Mutation profiles were generally tissue- but not dose-specific, suggesting that altered cellular folate status appears to interact with endogenous mutagenic mechanisms in each tissue to create a permissive context in which specific mutation types accumulate. These data illuminate potential mechanisms underpinning differences in observed associations between folate intake/status and cancer.